Thermal behavior of iron arsenides under non-oxidizing conditions - Seitkan, Ainur (2020)
Fe2As has been studied in situ by synchrotron powder X-ray diffraction (PXRD) over the range of temperatures 25–850 °C and under a neutral atmosphere to understand its thermal behavior, which is potentially important for gold extraction. For the first time, incongruent high-temperature reactions of Fe2As are observed as it breaks down and the existence of a previously undiscovered high-temperature FeAs phase with an NiAs-type structure has been determined experimentally. No evidence has been found for the existence of the high-temperature Fe3As2 phase. Hence, the previously published phase diagram for the Fe–As system has to be modified accordingly.